PENERAPAN ARSITEKTUR TROPIS PADA BANGUNAN SEKOLAH TINGGI ILMU KESEHATAN BAKTI NUSANTARA - Reynaldi R. Tuna; Abdi Gunawan Djafar; Niniek Pratiwi (Politeknik Kebangsaan, 2025)
The current development of educational institutions in the health sector still does not meet the number of health workers required. The way to get professional health workers is through formal education, which requires a higher education institution in the health sector in the form of a College of Health Sciences. The Bakti Nusantara Gorontalo Health Sciences College or STIKES BAKTARA Gorontalo is a form of secondary school from the Bakti Nusantara Gorontalo Health Vocational School. Currently, the Bakti Nusantara College of Health Sciences campus building still uses the Gorontalo Health Vocational School building as a place for lectures and administration activities. The condition of facilities and infrastructure to support the lecture process is limited, such as a lack of staff space to support administration, laboratory space to support learning and research infrastructure and classrooms to accommodate all STIKES BAKTARA Gorontalo students, while the number of students is increasing every year. Based on data from STIKES BAKTARA Gorontalo, in 2020 and 2021 the number of STIKES BAKTARA Gorontalo students experienced a significant increase, namely from 243 to 284 students. This causes the capacity to no longer match the number of students. The design of the College of Health Sciences in Gorontalo uses problem solving and programmatic methods with several stages such as describing the problem, formulating a solution and outlining the appropriate results and concepts. The design theme applied is tropical architecture with the aim of creating a building that can adapt to the climate conditions in Indonesia, namely the tropical climate, thereby creating comfort for its users.